The Effectiveness of the Sport "Dragon Boat Racing" in Reducing the Risk of Lymphedema Incidence: An Observational Study. Issue 4 (July 2019) - Iacorossi, Laura; Gambalunga, Francesca; Molinaro, Simona; De Domenico, Rosaria; Giannarelli, Diana; Fabi, Alessandra
Abstract : Background: Upper extremity lymphedema is a complication that often occurs in women with breast cancer as a result of surgery and/or radiotherapy. Some studies report that a boating activity known as the "dragon boat" sport can benefit these women. Aim: The aim of this study was to assess whether this type of sport prevents or reduces lymphedema, its impact on quality of life (QoL), and the possible predictors of this condition. Methods: This was an observational study of 2 groups: group A (women who participated in dragon boat racing for at least 6 months) and group B (women who participated in other forms of physical exercise biweekly). Data were collected at the National Cancer Institute of Rome and the lake of Castel Gandolfo from June to October 2016. The instruments used were a questionnaire created for sociodemographic and clinical data, the European Organisation for Research and Treatment of Cancer Core Questionnaire for evaluating QoL, and a tape measure applied to estimate the local lymphedema. Results: One hundred women participated in the study. Lymphedema incidence in group A was 4.0% (2 of 50), whereas in group B it was 26.0% (13 of 50). Women who participated in dragon boat racing also reported a healthier lifestyle, lower body mass index, and a better QoL (set point: 61.8 group B vs 80.0 group A). Conclusions: The dragon boat sport participants had more positive clinical and QoL outcomes than did the women who did not participate in that sporting activity. Implications for Clinical Practice: It would be important to make women with breast cancer aware of the practice of dragon boat racing.